Vital dye is enough for inguinal sentinel lymph node biopsy in melanoma patients - Oliveira Filho,Renato Santos de (2006)
PURPOSE: The importance of gamma probe detection (GPD) combined with vital dye for sentinel node (SN) biopsy is well accepted. We evaluated the efficacy of patent blue dye (PBD) in identifying inguinal SN. METHODS: Ninety-four cutaneous melanoma patients with inferior extremity lesions were submitted to SNB according to a established protocol. Patients were randomized in two groups: Blue group, where SN was identified by PPD and Probe group, where SN was identified by GPD. The median age was 44.2 years and median Breslow thickness was 2.1 mm. Preoperative lymphoscintigraphy, lymphatic mapping with PBD and intra-operative GPD was performed on all patients. Histological examination of SN consisted of hematoxylin-eosin and immunohistochemical staining. If micrometastases were present complete lymphadenectomy was performed. The SN was considered as identified by PBD if it was blue and identified by GPD if it demonstrated at least ten times greater radioactivity than background. RESULTS: It was explored 94 inguinal lymphatic basins, 145 SN were excised (70 guided primarily by blue dye and 75 guided primarily by probe). All SN identified by preoperative lymphoscintigraphy were excised. In the Blue group PPD identified all SN and all of them were hot. In the Probe group all SN were identified by probe and were blue. The coincidence of PPD and GPD was 100%. CONCLUSION: Patent blue dye is enough to identify superficial inguinal SN in cutaneous melanoma.